Ethnopharmacological Study of Medicinal Plants in Bajwat Wildlife Sanctuary, District Sialkot, Punjab Province of Pakistan - Sidra Ahsan Shah (Hindawi Limited, 2021)
Bajwat Wildlife Sanctuary is a complex riverine ecosystem and is unique because of the presence of river Chenab, various seasonal streams, lakes, and Head Marala barrage. These ecogeographic conditions provide diverse natural habitats for various plant and animal species to grow uninterrupted and have undocumented ethnopharmacologically important medicinal flora. The present study involves the first-ever extensive investigation to document the ethnopharmacological knowledge on medicinal plants of local healers and inhabitants of the Bajwat Wildlife Sanctuary to treat ailments. The unstructured and semistructured interviews of the local healers and inhabitants were conducted that included 130 individuals. The ethnomedicinal formulations, their method of preparation, mode of administration, parts of the plant used, diseases cured, and their categorization along with species use report (UR) were analyzed. The ethnopharmacological study led to the enlisting of 114 medicinal plant species belonging to 97 genera and distributed among 47 plant families. 2029 URs were collected with 42 general disease categories. Each plant species was reported 18 times to cure various diseases (∼18 UR), while ∼48 URs were collected on each disease category by local informants. Digestive issues (290 URs, ∼14.29%) and skin infections (279 URs, ∼13.75%) were found most commonly among the occupants of the area. The oral administration (69%) of herbal drugs and the preparation of plant extracts (32%) were the most common ethnopharmacological strategies. Inhabitants of the area were well aware of the limited use of poisonous plants. 8 (∼7%) out of the total 114 medicinal plant species were listed in the IUCN Red List of Threatened Species as Least Concern, while Eucalyptus camaldulensis Dehnh. was enlisted as near-threatened. The results of the present investigation show that the occupants of the Bajwat have sound information about the ethnopharmacological consumption of medicinal plants, and some of the novel ethnomedicinal formulations were reported which provide the basic data for further pharmacological research.